2018
DOI: 10.3390/ma11040584
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Low-Temperature N-Doped TiO2 Catalysts for Visible Light Photocatalytic Applications

Abstract: In this paper, TiO2 prepared with an aqueous sol-gel synthesis by peptization process is doped with nitrogen precursor to extend its activity towards the visible region. Three N-precursors are used: urea, ethylenediamine and triethylamine. Different molar N/Ti ratios are tested and the synthesis is adapted for each dopant. For urea- and trimethylamine-doped samples, anatase-brookite TiO2 nanoparticles of 6–8 nm are formed, with a specific surface area between 200 and 275 m2·g−1. In ethylenediamine-doped sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(114 citation statements)
references
References 58 publications
14
100
0
Order By: Relevance
“…This can be ascribed to the impurity states which are near the valence band edge, however, they do not act as charge carriers, and their role as recombination centres might be minimized [53]. As shown in Figure 2, the mixing of the p states of [71]. N-TiO 2 photocatalyst reduces the oxygen energy vacancies from 4.2 to 0.6 eV, suggesting that N favors the formation of oxygen vacancies [72].…”
Section: Non-metal Dopingmentioning
confidence: 97%
“…This can be ascribed to the impurity states which are near the valence band edge, however, they do not act as charge carriers, and their role as recombination centres might be minimized [53]. As shown in Figure 2, the mixing of the p states of [71]. N-TiO 2 photocatalyst reduces the oxygen energy vacancies from 4.2 to 0.6 eV, suggesting that N favors the formation of oxygen vacancies [72].…”
Section: Non-metal Dopingmentioning
confidence: 97%
“…A comparison with commercial Evonik P25 shows that the ZnCo2O4 based catalysts are more active under visible light with a PNP degradation rate three to six times higher than P25 for all samples (Figure 9). The PNP degradations can be compared to previous modified-TiO2 materials under similar photocatalytic conditions [53,54]: In these works, visible activated TiO2 doped with Fe and N reached 42 and 69% of PNP degradation respectively with the best materials after 24 h of visible illumination. In this work, the highest PNP degradation was obtained with ZnCo2O4/SnO2-20% reaching 67% after 24 h of illumination.…”
Section: Photocatalytic Performancementioning
confidence: 97%
“…The absorbance spectra were transformed using the Kubelka-Munk function [10,64,65] to produce a signal, normalized for comparison between samples, and so to calculated the band gaps (Eg,direct and Eg,indirect). The details of this treatment method have been widely described elsewhere [53,54,66].…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Recently, in order to make TiO 2 better use of the solar spectrum, several approaches, such us precious metal deposition, non-metallic or metallic elements doping, and semiconductor coupling, have been developed to deal with the insufficient of TiO 2 material [13][14][15][16][17]. Among them, element doping with metals and non-metals is considered as the simplest and inexpensive way.…”
mentioning
confidence: 99%
“…Among them, element doping with metals and non-metals is considered as the simplest and inexpensive way. For example, Julien G. Mahy et al [16] investigated the degradation activity of N-doped TiO 2 catalysts on p-nitrophenol, and the results showed that N-doped catalysts had a significantly improved degradation capability under visible light. Shafei and Sheibani [18] reported the preparation of Cu-doped TiO 2 -CNT nanocomposite powder and found that the catalyst exhibited great efficiency in the degradation rate of methylene blue under visible-light irradiation.…”
mentioning
confidence: 99%